Penerapan media kuis interaktif berbasis Kahoot! dalam pembelajaran sejarah untuk meningkatkan minat belajar siswa di SMA Panjura Malang - Edenia Tara Heriska; Aurinza Dinda Widhayanty; Slamet Sujud Purnawan Jati; Yuli Putra Wibawa (Historiography: Journal of Indonesian History and Education, 2023)
The use of learning media is one of the main points when learning history takes place. As well as in the use of learning media can better understand the material presented by educators. The selection of good and appropriate media can affect the process of successful learning of students. Along with the development of the technological era, it is increasingly advanced and sophisticated so that there are many opportunities in developing learning media. One of the problems that existed at Panjura High School in class X IPS 1 was the lack of use of learning media so that previously the lecture method was used which was felt to be less efficient in teaching history in class, causing little interest in student learning in History. With this, the researcher wants to apply learning media in the form of interactive quiz media based on Kahoot! as a means of evaluation, so that learning is more interesting and students become active. Media Kahoot! This is a game-based media which can contain questions that will be answered by students. This research was conducted in two cycles where the first cycle greatly influenced the continuation of the second cycle which became the determinant. With 15 selected respondents, then given a questionnaire via google form. Then the data is analyzed to see the success of implementing the Kahoot! media. in the process of learning history. The results showed that almost all students showed a positive response, namely in the first cycle it showed a percentage of 73.28 percent, then in the second cycle it produced a percentage of 90.78 percent for the application of Kahoot! media. during history lessons. With that the application of Kahoot media! can be said to be successful and experience an increase in student learning interest.Penggunaan media pembelajaran adalah salah satu hal yang poin utama pada saat pembelajaran sejarah berlangsung. Serta dalam penggunaan media pembelajaran dapat lebih memahami materi yang disampaikan oleh pendidik. Pemilihan media yang baik dan tepat dapat mempengaruhi proses keberhasilan belajar peserta didik. Seiring perkembangannya zaman teknologi semakin maju serta canggih sehingga banyak peluang dalam mengembangkan media pembelajaran. Salah satu permasalahan yang ada pada SMA Panjura di kelas X IPS 1Â  yaitu kurangnya pemanfaatan media pembelajaran sehingga sebelumnya menggunakan metode ceramah yang dirasa kurang efisien dalam pembelajaran sejarah di kelas sehingga menyebabkan sedikitnya minat belajar siswa dalam mata pelajaran Sejarah. Dengan hal ini peneliti ingin menerapkan media pembelajaran berupa media kuis interaktif berbasis Kahoot! sebagai sarana evaluasi, agar pembelajaran lebih menarik dan siswa menjadi aktif. Â Media Kahoot! ini merupakan media berbasis permainan yang didalamya dapat berisi soal-soal yang akan dijawab oleh peserta didik. Penelitian ini dilakukan dalam dua siklus dimana siklus pertama sangat mempengaruhi kelanjutan siklus kedua yang menjadi penentu. Dengan 15 responden yang dipilih, kemudian diberikan angket melalui google form. Kemudian data dianalisis guna melihat keberhasilan penerapan media Kahoot! dalam proses pembelajaran sejarah. Hasil menunjukkan hampir semua siswa menunjukkan respon positif yaitu pada siklus pertama menunjukkan persentase 73,28 persen kemudian pada siklus kedua menghasilkan persentase 90,78 persen terhadap penerapan media Kahoot! saat pembelajaran sejarah. Dengan tersebut penerapan media Kahoot! dapat dikatakan berhasil serta mengalami peningkatan minat belajar siswa.